Association of total cholesterol and atherosclerotic cardiovascular disease in patients with follicular thyroid cancer: A real-world study from Chinese populations. Issue 39 (1st October 2021) - Huang, Guoding; Lu, Hongquan; Li, Meigui; Lv, Qiongxiu; Chen, Qizhu
Abstract : Abstract: The association between serum total cholesterol (TC) level and incident atherosclerotic cardiovascular disease (ASCVD) in patients with follicular thyroid cancer postthyroidectomy is unknown. This was a retrospective study and patients (n = 384) were divided into low and high TC groups according to the median TC level. Incidence of composite ASCVD (myocardial infarction, ischemic stroke, and cardiovascular death) was compared between these 2 groups and factors contributing to the association of TC and ASCVD were evaluated. Patients in the high TC group were older and more likely to have diabetes and have higher C-reactive protein level. After thyroidectomy, serum levels of free triiodothyronine and free thyroxine were lower while thyroid-stimulating hormone level was higher in the high TC group. 31.6% and 39.7% of patients developed hypothyroidism in the low and high TC groups ( P < .05) postthyroidectomy. The incidence rate of composite ASCVD was higher in the high TC versus low TC groups, with incidence rate ratio of 1.69 (95% confidence interval [CI]: 1.07–2.69), which was mainly driven by a higher incidence rate of myocardial infarction in the high TC group (incidence rate ratio: 2.11 and 95% CI: 1.10–4.20). In unadjusted model, higher TC was associated with 73% higher risk of composite ASCVD. After adjustment for hypothyroidism, the association of higher TC and composite ASCVD was attenuated into insignificance, with hazard ratio of 0.92 and 95% CI: 0.81 to 1.34. Increased TC level was associated with composite ASCVD, which might be attributed to hypothyroidism postthyroidectomy. The use of levothyroxine might help to prevent hypercholestemia and reduce the incidence of ASCVD.